Familial hypomagnesemia with hypercalciuria and nefrocalcinosis due to a mutation in the CLDN16 gen (Claudina 16). A case report - Loza Munarriz, Reyner (2024)
We report the case of a girl with a history of seizures associated with persistent severe hypomagnesemia, hypocalcemia, hypercalciuria,  accompanied by alterations in renal function, metabolic acidosis and Nephrocalcinosis with progression to stage 5 chronic kidney disease (CKD) with a family history of chronic kidney disease, kidney stones and consanguinity of the parents, which is why the genetic study was carried out, resulting in a pathogenic mutation in homozygosity c.446 G>A (p.R149Q) located in exon 3 of the CLDN16 gene, which allows etiological diagnostic confirmation of a case of  Hypomagnesemia Familial with Hypercalciuria and Nephrocalcinosis (HFHNC), without severe ocular defects. In addition , the post-transplant evolution with good graft survival is presented.